Irrigation management on herbaceous cotton under semi-arid conditions of the Brazilian Northeast - Assis de Oliveira, Francisco; Gomes da Silva Campos, Tarcísio (Pesquisa Agropecuaria Brasileira, 1997)
During four years -1989/92 -, an experiment was carried out in an alluvial sandy loam soil, of the São Gonçalo Irrigation Project, at Sousa, PB, Brazil, with the objective of studying the effects of five timings from the last irrigation at 50 (E1), 65 (E2), 80 (E3), 95 (E4) and 110 (E5) days of the herbaceous cotton cultivar (Gossypium hirsutum L. r. latifolium Hutch) cycle, on cultivars CNPA Precoce 1, CNPA Acala 1, CNPA-6H and IAC-20. The experimental plan was a randomized complete block in a split-plot design, with four replications. The timing of the last irrigation E1, E2, E3, E4 and E5 promoted cotton yield of 2355, 3036, 3815, 4059 and 3720 kg/ha, with applied irrigation water amounts of 280, 426, 609, 714 and 830 mm, respectively. There were significant increases in the yield cotton up to treatment E3, with E2 > E1 (681 kg/ha) and E3 > E2 (779 kg/ha), but did not show significant difference between E3, E4 and E5. Treatment E3 promoted the maximum rate of marginal return (2.05), and treatment E4 contributed with maximum increase in liquid profit (R$ 866.00/ha). Herbaceous cotton IAC-20 with 3847 kg/ha and CNPA-6H with 3604 kg/ha yields did not differ, but were significantly more productive than the cultivars CNPA Precoce 1 (3222 kg/ha) and CNPA Acala 1 (2914 kg/ha). The timing of the last irrigation did not alter the culture cycle, but all cultivars completed their productive cycle 125 days after emergence. The medium results of culture yield in function of the timings of the last irrigation adapted to a square function, with R2 = 0.947**, showed that, at 95 days theoretically, the timing of the last irrigation would provide maximum yields.